2002
DOI: 10.1002/1521-3773(20021004)41:19<3648::aid-anie3648>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Bispyrene-Conjugated 2′-O-Methyloligonucleotide as a Highly Specific RNA-Recognition Probe

Abstract: In designing antisense molecules, it is crucial to detect the regions of the target RNA where the antisense molecule can hybridize. [1] To date, several studies have focused on the detection of these regions. The studies include theoretical calculations, [2] enzymatic digestion, [3] and DNA arrays, [4] and all of them have achieved a partial success. However, none of these methods have the potential to be applied to cells in which various endogenous molecules interact with RNA in a variety of manners.Solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 0 publications
3
51
0
Order By: Relevance
“…This was the idea of Yang et al in the construction of sensors for cations (Yang, Lin et al, 2001;Liao, Chen et al, 2002) when constructing a sensor for anions. Furthermore, since pyrene is a fluorophore that can easily form excimers, it has been used for the construction of sensors for DNA detection, as described by Mahara et al (Mahara, Iwase et al, 2002) as it needs the formation of pyreneconjugated oligonucleotides where excimers can occur or in sensor for protein-protein recognition, as described by Sahoo et al (Sahoo, Narayanaswami et al, 2000) Martins et al (Martins et al, 2011 in press) showed that peptide nanostructures containing pyrene derivatives sorbed onto them can sense distinct environments, with effect on fluorescence lifetimes, even when excimer are not formed. According to several authors, the challenge of developing these types of sensors is in the proposal of an all-serving-sensor.…”
Section: Fluorescence-based Biosensorsmentioning
confidence: 99%
“…This was the idea of Yang et al in the construction of sensors for cations (Yang, Lin et al, 2001;Liao, Chen et al, 2002) when constructing a sensor for anions. Furthermore, since pyrene is a fluorophore that can easily form excimers, it has been used for the construction of sensors for DNA detection, as described by Mahara et al (Mahara, Iwase et al, 2002) as it needs the formation of pyreneconjugated oligonucleotides where excimers can occur or in sensor for protein-protein recognition, as described by Sahoo et al (Sahoo, Narayanaswami et al, 2000) Martins et al (Martins et al, 2011 in press) showed that peptide nanostructures containing pyrene derivatives sorbed onto them can sense distinct environments, with effect on fluorescence lifetimes, even when excimer are not formed. According to several authors, the challenge of developing these types of sensors is in the proposal of an all-serving-sensor.…”
Section: Fluorescence-based Biosensorsmentioning
confidence: 99%
“…Mahara et al developed bispyrene probes that respond to RNA by excimer formation. 19 Kashida et al inserted two pyrene into ODNs with one or two intervening nucleotides to make the probes for deletion polymorphisms. 20 The ODN conjugate bearing two pyrenes on both of its terminus was synthesized by Fujimoto et al, as the MB based on excimer/monomer transformation.…”
Section: Excimermentioning
confidence: 99%
“…In order to overcome such disadvantages, our group has been proposing the direct detection of mRNA in the liquid phase (Mahara et al 2002). The detection technique has great advantages over the one in the solid phase in terms of the total process time.…”
Section: Introductionmentioning
confidence: 99%